Multifactorial individualised programme for hamstring muscle injury risk reduction in professional football: protocol for a prospective cohort study - Lahti, J.; Mendiguchia, J.; Ahtiainen, J.; Anula, L.; Kononen, T.; Kujala, M.; Matinlauri, A.; Peltonen, V.; Thibault, M.; Toivonen, R.-M.; Edouard, P.; Morin, J.-B. (BMJ Open Sport & Exercise Medicine, 2020)
Introduction Hamstring muscle injuries (HMI) continue to plague professional football. Several scientific publications have encouraged a multifactorial approach; however, no multifactorial HMI risk reduction studies have been conducted in professional football. Furthermore, individualisation of HMI management programmes has only been researched in a rehabilitation setting. Therefore, this study aims to determine if a specific multifactorial and individualised programme can reduce HMI occurrence in professional football.